Potensi Predasi Podisus nigrispinus (Hemiptera:Anthocoridae) terhadap Larva Spodoptera frugiperda (Lepidoptera: Noctuidae) - Muhammad Ade Dwidjaya; Marcellia RN; Miserani Miserani; Niranda Niranda; Putri Kiki Amelia (xxxx-xxxx, 2020)
Dwidjaya MA, Nauli MR, Miserani M, Niranda N, Amelia PK. 2020. Predation potential of podisus nigrispinus (Hemiptera: Anthocoridae) against larvae spodoptera frugiperda (Lepidoptera: Noctuidae). In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimalke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Spodoptera frugiperda is an important maize crop pest which has caused major losses to maize production.  This scientific work aims to see the potential predation of Podisus nigripinus against larvae of Spodoptera frugiperda.  This writing is done by analyzing the literature that will be developed into this paper.  Podisus nigripinus has been widely used in controlling larvae of the order lepidoptera, one of which is the larvae of Spodoptera frugiperda.  From the literature analysis study we conducted that the functional response of P. nigripinus predators varied in defense and density against prey Spodoptera Frugiperda, predators consumed more prey (prey) in the larval stage.